2004
DOI: 10.1097/01.ccm.0000089641.06306.68
|View full text |Cite
|
Sign up to set email alerts
|

Low caloric intake is associated with nosocomial bloodstream infections in patients in the medical intensive care unit*

Abstract: In the context of reducing risk of nosocomial bloodstream infections, failing to provide > or =25% of the recommended calories may be harmful. Higher caloric goals may be necessary to achieve other clinically important outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
200
2
12

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 338 publications
(222 citation statements)
references
References 42 publications
8
200
2
12
Order By: Relevance
“…The study, which investigated the impact of energy deficits on the microbiological results of blood cultures of long-term severely ill mechanical ventilation patients, confirms previous publications associating large energy deficits with infectious complications [12]. Interestingly, the cumulated energy deficits for patients developing methicillin-resistant Staphylococcus aureus blood stream infections (MRSA-BSI) were greater ([-300 kcal/day more) than those with ICU BSI caused by other pathogens.…”
supporting
confidence: 83%
“…The study, which investigated the impact of energy deficits on the microbiological results of blood cultures of long-term severely ill mechanical ventilation patients, confirms previous publications associating large energy deficits with infectious complications [12]. Interestingly, the cumulated energy deficits for patients developing methicillin-resistant Staphylococcus aureus blood stream infections (MRSA-BSI) were greater ([-300 kcal/day more) than those with ICU BSI caused by other pathogens.…”
supporting
confidence: 83%
“…Other factors related to malnutrition are decreased wound healing and tissue maintenance (White et al, 2012). According to a study by Rubinson, Diette, Song, Brower, and Krishnan (2004), patients that received less than 25% of their recommended calories a day were at an increased risk for nosocomial blood stream infections.…”
Section: Discussionmentioning
confidence: 99%
“…According to a study by Rubinson, Diette, Song, Brower, and Krishnan (2004), patients that received less than 25% of their recommended calories a day are associated with an increased risk for nosocomial blood stream infections.…”
Section: Enteral Feeding: Modes Of Deliverymentioning
confidence: 99%
“…Some papers have shown that in critical care settings, underfeeding related to inability to deliver the required nutrients is very common. Repetitive fasting periods, enteral tube complications, and gastrointestinal intolerance are the most frequent reported problems (4)(5)(6)(7)(8)(9)(10)(11). A multicentric study showed that the greater quantity of calories and proteins delivered the more significant clinical improvement is found especially in patients with body mass index (BMI) lower than 25 kg/m² or greater than 35 kg/m² (12).…”
Section: Introductionmentioning
confidence: 99%
“…Energy deficit is common in intensive care but only a few studies have correlated it with mortality among critically ill patients (5,6,11). In this context new data may enhance the perceptions of intensive care physicians on this important issue.…”
Section: Introductionmentioning
confidence: 99%